Congenital Extrahepatic Portosystemic Shunt: Abernethy Malformation Type 2 - Kaya, Mehmet Nur; Toprak, Ömer; Türel, Sultan; Ergün, Uğur; Arslan, Taha Yasin (European Journal of Therapeutics, 2023)
Abernethy malformation is a vascular congenital anomaly in which extrahepatic portocaval shunts develop. The patient was admitted to the gastroenterology department with complaints of abdominal pain and nausea. Ammonia and bilirubin levels were increased in the laboratory values and other liver function values were normal. The shunt was detected between the inferior vena cava and portal vein by ultrasonography and computed tomography, and the portal vein was hypoplastic. In this case report, we present a male patient diagnosed with Abernethy malformation type 2.